Quality in the management of educational institutions. The importance of internal organization (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2022)
This paper aims to define quality in educational institutions and understand that any internal organization requires elements of great importance, which are educational administration and management. This, in order to contribute to the formation of human beings capable of facing challenges throughout their lives.